THE EFFECTIVENESS OF THE GAMIFICATION-BASED JOYFUL LEARNING APPROACH IN IMPROVING ASMAUL HUSNA UNDERSTANDING - Nurun Nisa; Asdiana Asdiana; Maisarah Maisarah (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to analyze the effectiveness of gamification-based Joyful Learning in improving the understanding of Asmaul Husna. This study used a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The subjects of the study were 62 grade VII students at one of the Deli Serdang State Junior High Schools which were divided into experimental and control classes. Data were obtained through comprehension tests (pre-test and post-test), motivation questionnaires, and observations. The results showed that the average post-test score of the experimental class (82.3; SD = 6.4) was higher than the control class (74.1; SD = 7.1). The motivation score of students in the experimental class (M = 46.3) was also higher than that of the control class (M = 42.2). Independent t-tests showed significant differences (p < 0.05). These findings proved that gamification-based Joyful Learning was effective in increasing students' understanding and learning motivation. Although limited in the number of samples and time, this study opened up opportunities for the development of gamification in islamic religious education learning.